Conservation of Structural Timber Through Field Research in Timber Engineering - Masani, K. J. (Indian Forester, 1967)
Timber which is one of the important forest resources has of late been improperly used, adding to the already prevaillng shortage which could be overcome by various measures including regeneration at appropriate time, planting of quick-growing species, adopting improved logging and extraction methods, rational use of secondary species and utilization of small dimensioned stock for structural purposes. To attin the goal in respect of structural constructions, laboratory and field investigations have to be carried out for operational research leading to standardised designs for actual adoption resulting in timber conservation. In order to further augment the conservation programme, integrated schemes of law mills, seasning kilns and chemical preservation plants should be given practical shape as also the knowledge in Timber Engineering Science should be utilised for the purpose. With all these steps It would be established that a minimum conservation of 50% In timber and 80% in steel in a timber structural frame is made by adopting standardised structural units through modern Timber Engineering technique which ultimately help in keeping this natural resource, i.e., timber at a level which very nearly brings it at par with the demand. The paper deals with the results of laboratory Investigations, Field Research, Workshop fabrication technique, Demonstration structures observations and other relevant points worked out in the Timber Engineering Branch, Forest Research lnstitute, Dehra Dun (India) which lead to the ultimate conservation of timber. Based on these investigations and observations in the laboratory as well as in the field, other under-developed countries can also effect considerable conservation in their own forest resources by adopting modern Timber Engineering technique.